SISTEM INFORMASI PINJAMAN DANA PNPM-MANDIRI PADA UPK-BKM GINTUNG KERTA KARAWANG - abdussomad, Abdussomad (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
Abstract  –  UPK-BKM Gintung Kerta Karawang desperately need the existence of information systems that support in the process of fund loan services. therefore the author will discuss about the design of information systems loan at UPK-BKM Gintung Kerta Karawang.UPK BKM Gintung Kerta is a financial management unit at the Community Self-Help Agency which directly receives the PNPM-Mandiri Community Direct Fund (BLM) fund from the central level to be managed and distributed to the communities around the UPK area. Where the data processing is still using manual way bookkeeping, so it takes a long time in running the transaction processThe loan information system is the right solution to solve the problems of UPK-BKM Gintung Kerta Karawang, with the existence of the loan information system funds, will greatly assist the UPK in carrying out its duties and facilitate in solving problems that exist at the institution such as samples of data collection of borrowers, as well as with a computerized program can facilitate and accelerate the existing process so as to achieve effective and efficient activities